PENERAPAN METODE SENI GERAK DAN LAGU DALAM PEMBELAJARAN ANGGOTA TUBUH UNTUK MENINGKATKAN MOTORIK KASAR ANAK USIA DINI DI RA MIFTAHUL ULUM SUBANG - Siti Maemunah Inayatul Azizah; Yuwan Fijar Anugrah (CV. Kalimasada Group, 2025)
This study aims to improve the gross motor skills of early childhood through the application of the art of movement and song method at RA Miftahul Ulum Subang. Using classroom action research (PTK) with a quantitative approach and pretest-posttest design, the study involved 30 children aged 5–6 years divided into experimental and control groups. Data were collected through observation and video documentation. The results showed a significant improvement in children’s gross motor skills—from 63.63% (Developing as Expected) in cycle I to 80% (Developing Very Well) in cycle II. The art of movement and song method proved effective in enhancing children’s coordination, balance, and enthusiasm for learning